Online-Based Dietary Interventions as a Strategy for Overweight and Obesity Management: A Systematic Review - Defi Cintia Dewi; Radhiah Zakaria (Lembaga Pengembangan Kinerja Dosen, 2026)
Background: Wrong One of the current global public health challenges is obesity. This requires preventive efforts considering that obesity not only impacts health problems, but also social and economic problems. For these preventive efforts to be targeted, it is necessary to identify conventional and online obesity management. As time goes by, improving dietary patterns through behavior accompanied by effective online interventions can reduce the burden of disease. This study aims to see the effectiveness of online diets on weight loss. Methods: This study used a Systematic Review method approach to 18 articles selected through an electronic search in the form of Pubmed with keywords in the literature search using Medical subject headings (MeSH) with inclusion criteria: must include BMI measurements, participants in healthy conditions (not under treatment/having a disease) and received online diet intervention. Results: Online diet patterns are proven to reduce weight by 3-5% of the initial body weight or 3-6 kg from the initial body weight, meaning that each participant given online diet intervention is proven effective. Conclusion: weight loss programs through online media have been proven to be effective in reducing body weight if the intervention is given more frequently and for longer, which means that participants who visit the website more frequently to follow instructions on diet patterns and comply with the rules given will have a more significant weight loss rate.